Polymer dispersant, polymer dispersant composition, and carbon material dispersion

The polymer dispersant with a (meth)acryloyloxy group and quaternary ammonium salt ensures stable dispersibility and adhesion of carbon materials in liquid media, addressing dispersibility and coating film durability issues, and enhancing conductivity.

JP7612084B1Active Publication Date: 2025-01-10DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024035245
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-07
Publication Date
2025-01-10
Estimated Expiration
2044-03-07

AI Technical Summary

Technical Problem

Existing dispersants for carbon materials in liquid media suffer from insufficient dispersibility, re-agglomeration, thixotropic properties, and poor adhesion in ultraviolet-curable coatings, leading to instability and reduced performance of carbon material dispersions.

Method used

A polymer dispersant containing a specific structural unit with a (meth)acryloyloxy group, quaternary ammonium salt, and vinyl monomers, which provides excellent dispersibility, stability, and UV curability, allowing the dispersant to act as a crosslinking agent in ultraviolet-curable coatings.

Benefits of technology

The polymer dispersant achieves stable dispersibility of carbon materials at high concentrations, enhances storage stability and processability, and improves the durability and adhesion of coating films by acting as a crosslinking agent, while maintaining electrical and thermal conductivity properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612084000001
    Figure 0007612084000001
  • Figure 0007612084000002
    Figure 0007612084000002
  • Figure 0007612084000003
    Figure 0007612084000003
Patent Text Reader

Abstract

To provide a polymer dispersant for stably dispersing a carbon material in a liquid medium at a high concentration. [Solution] A polymer dispersant for dispersing a carbon material such as carbon black in a liquid medium, the polymer dispersant containing 45 mass % or more and 95 mass % or less of a structural unit (i) represented by the following general formula (1): TIFF0007612084000016.tif32170 (In the above general formula (1), R 1 and R 3 indicates a hydrogen atom, etc., and R 2 Ha-CH 2 CH 2 - or the like, m represents any number of repetitions, and n represents 10 to 100.) A polymer dispersing agent having 3% by mass or more and 45% by mass or less of structural units (ii) derived from a monomer which is a quaternary ammonium salt of a basic monomer such as 2-vinylpyridine, and 2% by mass or more and 10% by mass or less of structural units (iii) derived from a vinyl monomer copolymerizable with the structural units (i) and the structural units (ii), which is a polymer having a number average molecular weight of 10,000 or more and 30,000 or less, and which has ultraviolet curing properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer dispersant for stably dispersing a carbon material, and a carbon material dispersion obtained by using the polymer dispersant. [Background technology]

[0002] Carbon materials such as carbon black, carbon fiber, carbon nanotubes, graphite, and graphene (hereinafter simply referred to as carbon materials) have a six-membered ring graphite structure formed by covalent bonds of carbon atoms, and exhibit various properties such as electrical conductivity and thermal conductivity, and methods for utilizing these properties in a wide range of fields are being studied. For example, focusing on the electrical properties, thermal properties, and properties as a filler of carbon materials, their use as antistatic agents, conductive materials, plastic reinforcing materials, semiconductors, fuel cell electrodes, display cathode rays, etc. is being studied.

[0003] For these applications, a carbon material dispersion is required that has good dispersibility of the carbon material and maintains the dispersibility for a long period of time. However, nano-sized carbon materials have high surface energy and are prone to aggregation due to the strong van der Waals forces acting on them. For this reason, even if they are dispersed in a liquid medium, they often immediately aggregate.

[0004] In order to stably disperse carbon materials in liquid media, dispersants are generally used. For example, solvent-based dispersions of carbon nanotubes using cationic surfactants such as alkanolamine salts and polymer dispersants such as styrene-acrylic resins have been proposed (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2010-174084 A [Patent Document 2] Special Publication No. 2013-537570 Summary of the Invention [Problem to be solved by the invention]

[0006] However, when a low molecular weight surfactant is used as a dispersant, it is possible to disperse the carbon material in a liquid medium, but the dispersibility is not necessarily sufficient, and there is also the problem that the carbon material is easily re-aggregated. In addition, when a general polymer dispersant is used, the resulting dispersion tends to exhibit thixotropic properties, and the carbon material may settle or the dispersion may gel over time. Furthermore, when used in a UV-curable coating agent, the polymer dispersant that disperses the carbon material may not cure with UV light, which may deteriorate the strength and adhesion of the coating film.

[0007] The present invention has been made in consideration of the problems of the prior art, and the object of the present invention is to provide a polymeric dispersant for carbon materials that has excellent dispersibility even when the carbon material is contained at a high concentration, and that stably maintains dispersibility for a long period of time.Furthermore, the present invention is to provide a polymeric dispersant that, when used in an ultraviolet-curable coating agent or ink, has an ultraviolet-curable group in the polymeric dispersant, thereby eliminating components that are not incorporated into the coating film, and the ultraviolet-curable group allows the polymeric dispersant to act as a crosslinking agent, thereby improving the durability and adhesion of the coating film obtained from the coating agent or ink.Furthermore, the present invention is to provide a carbon material dispersion liquid with good dispersibility obtained by using the above-mentioned polymeric dispersant. [Means for solving the problem]

[0008] That is, according to the present invention, there is provided the following polymer dispersant. [1] A polymer dispersant for dispersing at least one carbon material selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite, and graphene in a liquid medium, comprising: The polymer dispersant contains 45% by mass or more and 95% by mass or less of a structural unit (i) having a (meth)acryloyloxy group bonded to an end thereof, which is represented by the following general formula (1):

[0009] [ka]

[0010] (In the above general formula (1), R 1 and R 3 represents a hydrogen atom or a methyl group, R 2 represents -CH2CH2- or -CH2CH2OCH2CH2-, m represents an arbitrary number of repetitions, and n represents 10 to 100. A polymer dispersing agent having ultraviolet curing properties, the polymer comprising: 3% by mass or more and 45% by mass or less of structural units (ii) derived from a monomer that is a quaternary ammonium salt of at least one basic monomer selected from the group consisting of 2-vinylpyridine, 4-vinylpyridine, 1-vinylimidazole, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate; and 2% by mass or more and 10% by mass or less of structural units (iii) derived from a vinyl-based monomer copolymerizable with the structural units (i) and the structural units (ii).

[0011] [2] The polymer dispersant according to [1], wherein the quaternary ammonium salt of the basic monomer is a benzyl chloride salt, a naphthyl methyl chloride salt, or an anthracenyl methyl chloride salt of the basic monomer. [3] The polymer dispersant according to [1] or [2], wherein the vinyl monomer that constitutes the structural unit (iii) contains α-methylstyrene, and the content of the structural unit derived from α-methylstyrene in the polymer is 0.5 mass% or more and 5 mass% or less. [4] A polymer dispersant composition comprising the polymer dispersant according to any one of [1] to [3] and a monomer represented by the following general formula (2):

[0012] [ka]

[0013] (In the general formula (2), R 4 represents an alkyl group having 1 to 18 carbon atoms; R 5 represents an alkylene group or a branched alkylene group having 2 to 4 carbon atoms; R 6 represents -CH2CH2- or -CH2CH2OCH2CH2-, and R 7 represents hydrogen or a methyl group, and p represents 10 to 100. [5] A carbon material dispersion comprising the polymer dispersant according to any one of [1] to [3], the carbon material, and the liquid medium. [6] The carbon material dispersion liquid according to [5], wherein the liquid medium contains at least one of ultraviolet-curable monomers and oligomers having one or more (meth)acryloyloxy groups. [7] The carbon material dispersion liquid according to [5] or [6], wherein a content of the polymer dispersant relative to 100 parts by mass of the carbon material is 10 parts by mass or more and 200 parts by mass or less, and a content of the carbon material relative to 100 mass% of the carbon material dispersion liquid is 15 mass% or less. Effect of the Invention

[0014] According to the present invention, it is possible to provide a carbon material dispersion liquid that has excellent dispersibility even when the carbon material is contained at a high concentration, and that maintains the dispersibility stably for a long period of time. The carbon material dispersion liquid of the present invention has excellent dispersibility, storage stability, viscosity characteristics, and processability, and can form a carbon coating film by coating or the like. In addition, by appropriately selecting the carbon material, a film with high transparency can be formed. Furthermore, even if the content of the polymer dispersant is small, the carbon material is dispersed in a good state, so that it is possible to form a coating film with a high content of the carbon material, and the properties of the carbon material itself, such as electrical conductivity and thermal conductivity, can be utilized. Furthermore, the polymer dispersant that disperses the carbon material has a group that is cured by ultraviolet light, and when used in an ultraviolet-curable coating agent or the like, the polymer dispersant can also be cured by ultraviolet light to increase the durability of the coating film. In addition, since the polymer dispersant has a large number of ultraviolet-curable groups, it acts as a crosslinking agent and can contribute to the durability of the coating film and the adhesion to the substrate in the same manner as described above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment. <Polymer dispersant> The polymer dispersant according to this embodiment is a polymer dispersant that disperses at least one carbon material selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite, and graphene in a liquid medium, and the polymer dispersant has 45% by mass or more and 95% by mass or less of structural units (i) having (meth)acryloyloxy groups bonded to their ends, as represented by the following general formula (1):

[0016] [ka]

[0017] In the general formula (1), R 1 and R 3 represents a hydrogen atom or a methyl group, R2 represents -CH2CH2- or -CH2CH2OCH2CH2-, m represents an arbitrary number of repetitions, and n represents 10 to 100. Furthermore, the polymer dispersant has 3% by mass or more and 45% by mass or less of structural units (ii) derived from a monomer that is a quaternary ammonium salt of at least one basic monomer selected from the group consisting of 2-vinylpyridine, 4-vinylpyridine, 1-vinylimidazole, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate, and 2% by mass or more and 10% by mass or less of structural units (iii) derived from a vinyl-based monomer copolymerizable with the structural units (i) and the structural units (ii), and is a polymer with a number average molecular weight of 10,000 or more and 30,000 or less, and is ultraviolet-curable.

[0018] The present embodiment is characterized by the above-mentioned configuration, in which the structural unit (i) of the general formula (1) is contained, and the graft-type polymer has a structure in which the polyalkylene glycol chain of the general formula (1) is grafted to the main chain, and the grafted polyalkylene glycol chain is highly contained within the range of 45% by mass to 95% by mass in the polymer dispersant. Furthermore, the main chain is characterized by the amino group of the vinyl monomer having an amino group having a quaternary ammonium salt of an organic halide, that is, the main chain contains a cationic group. By using the polymer dispersant according to the present embodiment, the carbon material can be dispersed in a liquid medium with low viscosity and without aggregation during storage. The cationic group of the main chain is adsorbed to the carbon material, and the grafted polyalkylene glycol chain causes steric repulsion between particles, and the carbon material can be dispersed well in the liquid medium.

[0019] Furthermore, the polymer dispersant is characterized in that the end of the grafted polyalkylene glycol chain in the polymer structure is bound to a radically polymerizable (meth)acryloxy group. When a UV-curable monomer or oligomer is used as a liquid medium and used in an active energy curable coating that can be cured by active energy such as UV or electron beam, particularly preferably an UV-curable coating, the polymer dispersant according to this embodiment reacts with the monomers of the liquid medium, and the polymer dispersant itself becomes a component of film formation. And, since the polymer dispersant has a plurality of (meth)acryloyloxy groups, it acts as a crosslinking agent and improves the durability or physical properties of the film.

[0020] The polymer dispersant according to this embodiment has 45% by mass or more and 95% by mass or less of structural units (i) having a (meth)acryloyloxy group bonded to the terminal, which are represented by the following general formula (1).

[0021] [ka]

[0022] In the general formula (1), R 1 and R 3 represents a hydrogen atom or a methyl group, R 2 represents -CH2CH2- or -CH2CH2OCH2CH2-, m represents an arbitrary number of repetitions, and n represents 10 to 100. This constitutional unit is a constitutional unit that becomes a branched graft chain of the polymer that is the polymer dispersant according to this embodiment. The structure is a polypropylene glycol chain, and the repeating unit n is 10 to 100, and the molecular weight of the graft chain is in the range of 580 to 5800. If the repeating unit n is less than 10, the grafted molecular weight is small, so sufficient steric repulsion cannot be exerted, and the dispersion stability of the carbon material may not be obtained. On the other hand, if the repeating unit n is more than 100, the monomer that constitutes it has a large molecular weight, so that it may remain poorly polymerized when producing the polymer dispersant, or the viscosity of the dispersion may increase. Particularly preferably, the repeating unit n is 17 to 51, and the molecular weight of the graft chain is 1000 to 3000.

[0023] The polypropylene glycol chain has the above-mentioned chain, and the end of the chain is bonded to a (meth)acryloyl group via a urethane bond, with -CH2CH2- or -CH2CH2OCH2CH2- as a linking group. Since the end is a (meth)acryloyloxy group, when the polymer dispersant according to the present embodiment is used in an ultraviolet-curable coating agent, the (meth)acryloyloxy group is polymerized, and the ultraviolet-curable monomer or oligomer contained in the coating agent and the polymer dispersant react by radical polymerization. This allows the polymer dispersant to undergo a crosslinking reaction and become a coating film component. In addition, the polymer dispersant contains a large amount of (meth)acryloyloxy groups, which act as a crosslinking agent and contribute to the adhesion of the coating film component or durability such as abrasion resistance.

[0024] One end is bonded to the main chain as an ester group, forming a graft structure. This constituent unit (i) is introduced into the polymer dispersant by the following method. That is, first, poly(n=10-100)propylene glycol mono(meth)acrylate is used as a monomer unit and polymerized with other monomers to form a constituent component. Then, one hydroxyl group of the polypropylene glycol mono(meth)acrylate is reacted with (meth)acryloyloxyethyl isocyanate or (meth)acryloyloxyethoxyethyl isocyanate, thereby introducing this constituent unit (i) into the polymer dispersant as a graft chain.

[0025] A major feature is that the amount of raw material that becomes this structural unit (i) is 45% by mass or more and 95% by mass or less of the total raw materials of the polymer dispersant. By containing a large amount of this structural unit, the dispersion stability of the carbon material can be increased by steric hindrance. If this amount is less than 45% by mass, sufficient dispersion stability cannot be obtained. On the other hand, if this amount is more than 95% by mass, when an attempt is made to introduce an amount that constitutes this structural unit, the molecular weight of polypropylene glycol mono(meth)acrylate is large, so that it is poorly polymerizable during the production of the polymer dispersant, and it may remain unpolymerized. This amount is preferably 50% by mass or more and 90% by mass or less, and more preferably 51% by mass or more and 85% by mass or less. 。

[0026] Next, examples of units constituting the polymer dispersant according to this embodiment include a constituent unit (ii) derived from a monomer that is a quaternary ammonium salt of at least one basic monomer selected from the group consisting of 2-vinylpyridine, 4-vinylpyridine, 1-vinylimidazole, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate. This constituent is a quaternary ammonium salt, and is a group that adsorbs to a carbon material composed of a carbon aromatic six-membered ring through ionic interaction with the carbon material, and further through ππ stacking when the counter ion is an aromatic ring.

[0027] The monomer is a quaternary ammonium salt of at least one basic monomer selected from the group consisting of 2-vinylpyridine, 4-vinylpyridine, 1-vinylimidazole, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate. The counter ion is a counter ion of a quaternary ammonium salt in which an alkyl halide such as chlorine, bromine, or iodine, or an arylmethyl halide forms a salt with a tertiary amino group. Specific examples include alkyl halides such as methyl chloride, methyl bromide, methyl iodide, and lauryl chloride, benzyl chloride, benzyl bromide, benzyl iodide, naphthyl methyl chloride, and anthracenyl methyl chloride. In particular, in this embodiment, a counter ion having an aromatic ring is preferred in order to enhance the adsorption to the carbon material consisting of the six-membered aromatic ring. Furthermore, in consideration of colorability, it is preferable to use at least one selected from the group consisting of benzyl chloride, naphthyl methyl chloride, and anthracenyl methyl chloride as the counter ion.

[0028] The amount of the raw material that becomes this constituent unit (ii) needs to be 3% by mass or more and 45% by mass or less of the total raw materials of the polymer dispersant. If this amount is less than 10% by mass, the number of adsorption groups will be small, sufficient adsorption cannot be obtained, and dispersion stability may not be obtained. On the other hand, if this amount is more than 45% by mass, the ionicity is too high, and when it is blended with the coating agent, it may not be soluble in the liquid medium and cannot be mixed with the coating agent. This amount is preferably 10% by mass or more and 42% by mass or less, and more preferably 11.5% by mass or more and 40.5% by mass or less.

[0029] The polymer dispersant according to the present embodiment contains a constituent unit (iii) derived from a vinyl monomer copolymerizable with the constituent unit (i) and the constituent unit (ii). The vinyl monomer is another monomer component for improving the polymerizability of the constituent unit (i) and the constituent unit (ii) with the raw material components, polymerizing the constituent components without leaving them, or for adjusting the molecular weight or improving the adsorption. As the vinyl monomer, a conventionally known vinyl monomer capable of radical polymerization, such as a styrene monomer, (meth)acrylic acid, (meth)acrylate, (meth)acrylamide monomer, and (meth)acrylonitrile, can be used. The polymer dispersant can also contain 2-vinylpyridine, 4-vinylpyridine, 1-vinylimidazole, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate, which are not in the form of the quaternary ammonium salt, as described above. In this way, by containing an amino group, when a carboxyl group is present on the surface of the carbon material, it can be adsorbed by ionic bond.

[0030] The amount of the raw material for the structural unit (iii) is the remaining amount of the raw materials for the structural unit (i) and the structural unit (ii), and in this embodiment, it is necessary that it is 2% by mass or more and 10% by mass or less of the total raw materials of the polymer dispersant. In particular, in this embodiment, it is preferable that the vinyl monomer for the structural unit (iii) contains α-methylstyrene from the viewpoint of adjusting the molecular weight and introducing an aromatic ring into the main chain. In addition, it is preferable that the content of the structural unit derived from α-methylstyrene in the polymer is 0.5% by mass or more and 5% by mass or less. α-Methylstyrene can reduce the polymerizability by generating a tertiary carbon radical to which an aromatic group is bonded during polymerization, and adjust the molecular weight to a predetermined molecular weight. In addition, it is possible to introduce an aromatic ring into the main chain, which can contribute to the adsorption property with the carbon material. In addition, if the content is less than 0.5% by mass, the molecular weight cannot be adjusted, and if the content is more than 5% by mass, the polymerizability may be reduced too much, resulting in a deterioration in the polymerization yield. The content is more preferably 0.8% by mass or more and 3% by mass or less.

[0031] The polymer dispersant according to this embodiment is a polymer having a number average molecular weight of 10,000 or more and 30,000 or less. If the number average molecular weight is less than 10,000, the main chain of the graft structure has a small molecular weight, so that even if the dispersant is adsorbed, it may be detached, and dispersion stability may not be obtained. On the other hand, if the number average molecular weight is more than 30,000, the molecular weight may be too large and the viscosity of the dispersion may be increased. The number average molecular weight is preferably 12,000 or more and 25,000 or less. The number average molecular weight is the number average molecular weight in terms of polystyrene using gel perchromatography.

[0032] The above is the polymer dispersant according to the present embodiment, and the manufacturing method thereof is not particularly limited. A preferred example is described below, but is not limited thereto. The manufacturing method of the polymer dispersant according to the present embodiment is preferably solution polymerization. Using a polymerization solvent, the above-mentioned polypropylene glycol mono(meth)acrylate and monomers serving as raw materials for the structural unit (ii) and the structural unit (iii) are polymerized by thermal polymerization using a conventionally known azo-based radical polymerization initiator such as azobisisobutyronitrile or a peroxide-based radical polymerization initiator such as benzoyl peroxide. After the polymerization is completed, as described above, (meth)acryloyloxyethyl isocyanate or the like is added to introduce a radically polymerizable (meth)acryloyloxy group to the end of the polypropylene glycol chain to obtain the polymer. Alternatively, polypropylene glycol mono(meth)acrylate, at least one basic monomer selected from the group consisting of 2-vinylpyridine, 4-vinylpyridine, 1-vinylimidazole, dimethylaminoethyl(meth)acrylate, and diethylaminoethyl(meth)acrylate, and a monomer serving as a raw material for the structural unit (iii) may be polymerized, and then a quaternizing agent such as an alkyl halide may be added to convert the amino group of the basic monomer into a quaternary ammonium salt, followed by introducing a radically polymerizable group into the terminal.

[0033] The solvent used in the solution polymerization is a conventionally known organic solvent, and is not particularly limited. Specifically, one or more of solvents such as hydrocarbons, ketones, esters, glycols, glycol esters, amides, sulfoxides, carbonates, and ionic liquids can be used. Although these organic solvents may be used, they are not environmentally friendly as volatile organic solvents (VOCs), and when used in an ultraviolet-curable coating agent, the coating agent is an environmentally friendly coating agent because all of its constituent components become film components, so it is not preferable to contain an organic solvent in the polymer dispersant according to this embodiment. Therefore, as the solvent used in the polymerization, it is preferable to use a polyglycol-based solvent of poly (n = 4 or more), which is a non-volatile solvent, has a relatively large molecular weight, and can dissolve the polymer dispersant according to this embodiment. Specifically, polyethylene glycol monoalkyl ether, polypropylene glycol monoalkyl ether, polyethylene propylene glycol monoalkyl ether, polyethylene glycol dialkyl ether, etc. can be mentioned. By using this polyglycol-based solvent, it is possible to make it non-volatile.

[0034] However, although the polyglycol-based solvent is non-volatile, it cannot be incorporated into the coating film and acts plastically, which may deteriorate the physical properties of the coating film. Therefore, the polymer dispersant composition according to this embodiment is preferably a composition of the polymer dispersant according to this embodiment and a monomer represented by the following general formula (2).

[0035] [ka]

[0036] In the general formula (2), R 4 represents an alkyl group having 1 to 18 carbon atoms; R 5 represents an alkylene group or a branched alkylene group having 2 to 4 carbon atoms; R 6 represents -CH2CH2- or -CH2CH2OCH2CH2-, and R 7represents hydrogen or a methyl group, and p represents 10 to 100.

[0037] The monomer represented by the general formula (2) is R 5 It is a monomer having a structure in which one end of poly(p=10-100) alkylene glycol having ethylene, propylene, methylethylene, or tetramethylene groups is an alkyl ether having a carbon number ranging from a methyl group to an octadecyl group, and the other end has a (meth)acryloyloxy group bonded with -CH2CH2- or -CH2CH2OCH2CH2- via a urethane bond. This monomer has a relatively large molecular weight, is nonvolatile, and has a radically polymerizable (meth)acryloyloxy group at the end, which allows it to become a component of a coating film.

[0038] This monomer component is obtained by using a polyalkylene glycol monoalkyl ether having 10 to 100 repeating units as a solvent when polymerizing the polymer dispersant of this embodiment, polymerizing the polymer dispersant of this embodiment, and then reacting it with (meth)acryloyloxyethyl isocyanate or the like when adding a radically polymerizable group to the end of the polymer dispersant of this embodiment. At the same time, the (meth)acryloyloxyethyl isocyanate or the like is reacted with the hydroxyl group at one end of the polyalkylene glycol monoalkyl ether used as the solvent, thereby converting the polyalkylene glycol monoalkyl ether, which is the solvent, into a radically polymerizable monomer of general formula (2).

[0039] The polyalkylene glycol monoalkyl ether used has a repeating unit p of 10 to 100. If the repeating unit p is less than 10, it may contain an oligomer-like molecular weight that produces a flash point, while if the repeating unit p is more than 100, the viscosity may increase and polymerization may become incomplete. The repeating unit p is preferably 15 to 50. Specific examples of the polyalkylene glycol monoalkyl ether include polyethylene glycol monomethyl ether, polypropylene glycol monomethyl ether, and polyethylene glycol polypropylene glycol monobutyl ether. Polyethylene glycol polypropylene glycol monobutyl ether is preferred, as it is liquid at room temperature and is commercially available in a wide variety of molecular weight ranges.

[0040] In the composition of the polymer dispersant and the monomer represented by the general formula (2) according to the present embodiment, the content of the polymer dispersant is arbitrary and is not particularly limited, but the content of the polymer dispersant is preferably 30% by mass or more and 70% by mass or less. The reaction of the isocyanate and hydroxyl group of the above-mentioned polymer dispersant, polyalkylene glycol monoalkyl ether, and (meth)acryloyloxyethyl isocyanate or the like is obtained by a conventionally known method and is not particularly limited. It can be obtained by reacting with heat or by reacting with tin laurate, amine, or the like as a catalyst.

[0041] <Carbon materials> The polymer dispersant according to this embodiment is a polymer dispersant that disperses at least one carbon material selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite, and graphene in a liquid medium. Examples of the carbon material used in this embodiment include carbon black, carbon fiber, carbon nanotube, graphite, and graphene. The details of these materials are not particularly limited. For example, acetylene black, furnace black, thermal black, and ketjen black can be used as carbon black. There are no particular limitations on the structure, oil absorption, specific surface area, or surface modification such as oxidation, and various conventionally known carbon blacks can be used.

[0042] Examples of carbon fibers include PAN-based carbon fibers made from polyacrylonitrile, pitch-based carbon fibers made from pitches, and recycled products thereof. In particular, so-called carbon nanofibers, which have a nano-sized fiber diameter and a cylindrical shape formed by rolling up a hexagonal graphite structure, and carbon nanotubes, which have a single nano-sized diameter, can be used. Regarding carbon nanofibers or carbon nanotubes, multi-walled or single-walled carbon nanofibers can be used.

[0043] Graphite and graphene, which are nanosheets each having one to several carbon layers, can be used. The above carbon materials are not limited in particle size, fiber size, fiber length, shape, or manufacturing method. Mixtures of these materials can also be used. The carbon materials may be doped with other metals such as platinum and palladium or metal salts.

[0044] Furthermore, the surface of these carbon materials may be modified by oxidation, plasma treatment, radiation treatment, corona treatment, coupling treatment, or the like.

[0045] <Carbon material dispersion> This embodiment is characterized by a carbon material dispersion (hereinafter also simply referred to as dispersion) containing the above-mentioned carbon material, liquid medium, and polymer dispersant, characterized in that the polymer dispersant is the polymer dispersant according to this embodiment. As the liquid medium, the above-mentioned conventionally known organic solvent is used. Particularly preferably, the liquid medium used in this embodiment is one that allows the carbon material dispersion according to this embodiment to be used in an ultraviolet-curable coating agent, and the liquid medium is preferably a mixed liquid containing at least one of ultraviolet-curable monomers and oligomers having one or more (meth)acryloyloxy groups.

[0046] The mixture containing at least one of the ultraviolet curable monomers and oligomers may be any conventionally known material, and is not particularly limited. Specific examples of the curable components include monofunctional monomers, polyfunctional monomers, photocurable oligomers, and photocurable polymers. More specifically, examples of the monofunctional monomer include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, adamantyl (meth)acrylate, adamantyl methyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, ) acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polyethylene glycol monomethyl ether (meth)acrylate, 2-ethoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, allyl (meth)acrylate, vinyloxyethoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, an adduct of phthalic anhydride and 2-hydroxyethyl (meth)acrylate, and acryloylmorpholine are examples of radical polymerizable monomers.

[0047] Examples of the polyfunctional monomer or photocurable oligomer include neopentyl glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, poly(n=2 or more) ethylene glycol di(meth)acrylate, polypropylene glycol (n=2 or more) di(meth)acrylate, polybutylene glycol (n=2 or more) di(meth)acrylate, 2,2-bis(4-(meth)acryloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, trimethylolpropane diacrylate, bis(2-(meth)acryloxyethy (meth)-hydroxyethyl-isocyanurate, trimethylolpropane tri(meth)acrylate, tris(2-(meth)acryloxyethyl)isocyanurate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy poly(meth)acrylates such as epoxy di(meth)acrylates obtained by reacting bisphenol A diepoxy with (meth)acrylic acid, 1,Urethane tri(meth)acrylate obtained by reacting 2-hydroxyethyl(meth)acrylate with a trimer of 6-hexamethylene diisocyanate, urethane di(meth)acrylate obtained by reacting isophorone diisocyanate with 2-hydroxypropyl(meth)acrylate, urethane hexa(meth)acrylate obtained by reacting isophorone diisocyanate with pentaerythritol tri(meth)acrylate, urethane di(meth)acrylate obtained by reacting dicyclohexyl diisocyanate with 2-hydroxyethyl(meth)acrylate, dicyclo Examples of the urethane poly(meth)acrylate include urethane di(meth)acrylate obtained by reacting a urethane reaction product of hexyl diisocyanate and poly(n=6-15)tetramethylene glycol with 2-hydroxyethyl(meth)acrylate, polyester (meth)acrylate obtained by reacting trimethylolethane with succinic acid and (meth)acrylic acid, and polyester poly(meth)acrylate such as polyester (meth)acrylate obtained by reacting trimethylolpropane with succinic acid, ethylene glycol, and (meth)acrylic acid.

[0048] The photocurable polymer is a polymer having a plurality of radically polymerizable (meth)acryloyloxy groups at its terminal or side chain in a polymer such as poly(meth)acrylate, polyurethane, polyester, polyamide, polyimide, or polyepoxy resin, and the monomer species of the polymer, the obtained polymer, and the photocurable polymer obtained by imparting photopolymerization to the polymer are not particularly limited. Furthermore, a photocurable polymer having alkali developability due to the presence of a carboxyl group or the like can also be used.

[0049] The above is the configuration of the carbon material dispersion liquid according to the present embodiment, and it is preferable that the mass ratio of the carbon material and the polymer dispersant according to the present embodiment is 10 parts by mass or more and 200 parts by mass with respect to 100 parts by mass of the carbon material, and the content of the carbon material in the carbon material dispersion liquid is 15% by mass or less. If the amount of the polymer dispersant is too small with respect to the carbon material, it tends to be difficult to obtain sufficient dispersion performance. On the other hand, if the amount of the polymer dispersant is too large with respect to the carbon material, the dispersion liquid may become thickened, and the ratio of the carbon material in the solid content tends to become relatively low. Therefore, the mass of the polymer dispersant with respect to 100 parts by mass of the carbon material in the carbon material dispersion liquid according to the present embodiment is preferably 10 parts by mass or more and 200 parts by mass or less, more preferably 20 parts by mass or more and 150 parts by mass or less, and particularly preferably 30 parts by mass or more and 100 parts by mass or less. The content of the carbon material in the carbon material dispersion liquid is preferably 15% by mass or less, and more preferably 0.01% by mass or more and 10% by mass or less. By using the polymer dispersant according to this embodiment, and more preferably by blending the carbon material and the polymer dispersant in the above-mentioned mass ratio, a more stably dispersed carbon material dispersion liquid can be obtained.

[0050] The carbon material dispersion liquid according to the present embodiment may contain other components in addition to the above-mentioned carbon material, polymer dispersant, and liquid medium. Specifically, the carbon material dispersion liquid may contain a photopolymerization initiator, a light stabilizer, an antioxidant, a dye, a pigment, a fluorescent brightening agent, a leveling agent, an antifoaming agent, a lubricant, a thickener, an antistatic agent, a surfactant, a silane coupling agent, an anti-yellowing agent, a bluing agent, an infrared absorbing agent, an adhesion promoter, an antifouling agent, a water repellent agent, a curing catalyst, an inorganic filler such as silica, and metal fine particles.

[0051] Among them, photopolymerization initiators include carbonyl compounds such as benzoin, benzoin monomethyl ether, benzoin isopropyl ether, acetoin, benzil, benzophenone, p-methoxybenzophenone, diethoxyacetophenone, benzil dimethyl ketal, 2,2-diethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, methylphenyl glyoxylate, and 2-hydroxy-2-methyl-1-phenylpropan-1-one; sulfur compounds such as tetramethylthiuram monosulfide and tetramethylthiuram disulfide; Examples of such compounds include phosphate compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and the like; as well as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 and camphorquinone. These are selected according to the wavelength of the curing light, and in some cases, multiple types are used.

[0052] The above are the main components of the carbon material dispersion liquid according to this embodiment, and the composition of each component is determined depending on the application, so the other components are not limited in the present invention. Conventionally known compositions and materials are used. As other additives, conventionally known ones can be used and are not particularly limited. Specifically, photopolymerization initiators for photocuring, organic solvents for adjusting the viscosity and applicability of the coating material, etc. are used and are not limited.

[0053] The physical properties of the carbon material dispersion according to the present embodiment are conventionally known and are not particularly limited. From the practical standpoint, the viscosity of the carbon material dispersion is preferably 3 mPa·s or more and 100 mPa·s or less.

[0054] The method of dispersing the carbon material using the polymer dispersant described above when preparing the carbon material dispersion liquid according to this embodiment is not limited, and can be carried out by a conventionally known method. For example, a dispersion method such as dispersion using a disperser, kneading with a three-roll mill, ultrasonic dispersion, bead mill dispersion, an emulsifier, or a high-pressure homogenizer can be used. Among these, bead mill dispersion, ultrasonic dispersion, or a high-pressure homogenizer is preferred because of its high dispersion effect. The carbon material dispersion liquid according to this embodiment can be easily prepared by mixing at least the carbon material, the liquid medium, and the polymer dispersant, and performing a dispersion process.

[0055] The method for confirming the dispersibility of the carbon material in the carbon material dispersion liquid according to this embodiment can be carried out by a method for measuring the absorbance of the dispersion liquid using a spectrophotometer as described below. First, several samples of a dispersion liquid with a very low concentration of carbon material with a known concentration are prepared, and the absorbance at a specific wavelength is measured to create a calibration curve of the absorbance versus concentration. Next, the carbon material, the liquid medium, and the polymer dispersant are mixed and dispersed using a predetermined dispersion method, and then centrifuged to separate the carbon material that cannot be dispersed by settling, and the supernatant is diluted to a concentration at which the absorbance can be measured, and the absorbance is measured, and the concentration is calculated from the calibration curve. The dispersibility can be evaluated by comparing the concentration of the dispersion liquid obtained and the amount of the dispersion liquid. In addition, a method of leaving the carbon material dispersion liquid after centrifugation stationary for a long period of time and confirming the presence or absence of aggregates can also be carried out. In addition, the dispersion liquid may be dropped onto a glass plate or the like and its state may be confirmed using an electron microscope or the like, or it may be coated to prepare a film and its electrical conductivity or the like may be measured to determine that the dispersion is good when it reaches a predetermined electrical conductivity.

[0056] The carbon material dispersion liquid according to the present embodiment can be used for applications such as paints, inks, or plastics in which the carbon material is dispersed, and is expected to be used as an electrically conductive material or a thermally conductive agent, as well as an antistatic material. A paint or ink in which the carbon material is dispersed can be produced by adding a solvent, a resin, an additive, or the like to the carbon material dispersion liquid according to the present embodiment to produce a paint or ink composition, or by adding the carbon material dispersion liquid to a commercially available paint or ink. EXAMPLES

[0057] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified. <Synthesis of polymer dispersant (polymer)>

[0058] (Synthesis Example 1) a) Polymerization In a reaction apparatus equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, 71.0 parts (0.0400 mol) of polypropylene glycol polyethylene glycol monobutyl ether (trade name "UNILUBE 50MB-26", NOF Corporation, molecular weight: 1776, repeating units: propylene glycol 17, ethylene glycol 17, hereinafter abbreviated as 50MB-26), 70 parts (0.0342 mol) of one-terminated methacryloyloxy polypropylene glycol (trade name "BLEMMER PP-2000D", NOF Corporation, molecular weight: 2048, repeating units about 33.8, hereinafter abbreviated as PP2000D), 1.2 parts of α-methylstyrene (hereinafter abbreviated as αMS), 9.4 parts of styrene (hereinafter abbreviated as St), and 19.4 parts of 4-vinylpyridine (hereinafter abbreviated as 4VP) were placed, and the mixture was heated to 75° C. while bubbling nitrogen gas. When the temperature reached 70°C, 4.5 parts of 2,2'-azobis(isobutyric acid)dimethyl (trade name "V-601", manufactured by Wako Pure Chemical Industries, Ltd., hereinafter abbreviated as V601) were added as a polymerization initiator, and polymerization was carried out at 75°C for 4 hours. Furthermore, 2.0 parts of V601 were added, and polymerization was carried out at 75°C for 4 hours to obtain a polymer solution. The obtained polymer was sampled and the molecular weight was measured by gel permeation chromatography using polystyrene standards with tetrahydrofuran as an eluent. The number average molecular weight (hereinafter abbreviated as Mn) was 22,100, the molecular weight distribution (weight average molecular weight / number average molecular weight, hereinafter abbreviated as PDI) was 1.85, the peak top molecular weight (hereinafter abbreviated as PT) was 38,400, and almost no peaks derived from PP2000D used as a raw material were observed. The molecular weight was measured in the same manner as below.

[0059] b) Introduction of unsaturated groups Next, 11.5 parts (0.0742 mol, total number of moles of 50MB-26 and PP2000D) of 2-isocyanatoethyl methacrylate (trade name "Kalends MOI", Showa Denko KK, molecular weight: 155.15, hereinafter abbreviated as MOI) and 0.3 parts of dioctanoic acid tin (hereinafter abbreviated as DOS) as a catalyst were added to the polymer solution obtained above, and the reaction was carried out at 80 ° C. for 5 hours. When the sample was sampled and measured with an infrared spectrophotometer, the peak derived from the isocyanate group disappeared, and it was confirmed that the reaction was completed. Therefore, a polymer solution in which unsaturated groups were introduced into the polymer terminals and the terminals of 50MB-26 was obtained.

[0060] c) Quaternary chloride Further, 31.0 parts of 1-chloromethylnaphthalene (hereinafter abbreviated as CMN) and 137.5 parts of 50MB-26 were added to the above-obtained polymer solution into which unsaturated groups had been introduced, and the reaction was carried out at 90°C for 5 hours. The amine value was measured by sampling and found to be 0.5 mgKOH / g (value as polymer solution), confirming that the quaternary salt conversion proceeded almost exactly as expected. The amine value was measured and calculated using a 0.1N 2-propanol hydrochloric acid solution with a potentiometric automatic titrator. The amine value was calculated in the same manner below. The molecular weight of the obtained polymer was measured by sampling and found to be Mn 23,500, PDI 1.92, and PT 39,400. The obtained polymer solution containing the polymer dispersant of the present invention is called VG-1. The theoretical solid content of the polymer dispersant calculated from the blending ratio in this polymer is 40.0%. The theoretical solid content was calculated by dividing the solid content by the total amount, taking the components excluding the solvent 50MB-26 and the reaction product of 50MB-26 and MOI as the solid content.

[0061] (Synthesis Examples 2 to 5) Polymer solutions containing the polymer dispersant of the present invention were obtained in the same manner as in the above-mentioned Synthesis Example 1, except that the compositions were as shown in Table 1. The physical properties of the obtained polymer solutions VG-2 to VG-5 are shown in Table 1.

[0062] The meanings of the abbreviations in Table 1 are as follows: AP1000D: One-terminated methacryloyloxy polypropylene glycol (product name "Blenmar AP-1000D", NOF Corporation, molecular weight: 1060, repeat unit approx. 17) 2VP: 2-vinylpyridine VI: 1-Vinylimidazole ·DMAEMA: 2-N,N-dimethylaminoethyl methacrylate MMA: Methyl methacrylate AOI: 2-isocyanatoethyl acrylate (product name "Kalends AOI", manufactured by Showa Denko Co., Ltd., molecular weight: 155.15 BzCl: Benzyl chloride CMA: 9-chloromethylanthracene

[0063] [Table 1]

[0064] (Comparative Synthesis Example 1) Polymer dispersant containing no unsaturated groups In a reaction apparatus similar to that of Synthesis Example 1 equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, 71.0 parts (0.0400 mol) of 50MB-26, 70 parts (0.0342 mol) of PP-2000D, 1.2 parts of αMS, 9.4 parts of St, and 19.4 parts of 4VP were placed in the reaction apparatus, and heated to 75°C while bubbling nitrogen gas. When the temperature reached 70°C, 4.5 parts of V601 were added as a polymerization initiator, and polymerization was carried out at 75°C for 4 hours. Furthermore, 2.0 parts of V601 were added, and polymerization was carried out at 75°C for 4 hours to obtain a polymer solution. The polymer was sampled and the molecular weight of the obtained polymer was measured, and the number average molecular weight (hereinafter abbreviated as Mn) was 21,600, the PDI was 1.84, and the PT was 37,200, and almost no peaks derived from the PP2000D used as the raw material were observed.

[0065] c) Quaternary ammonium chloride Next, 31.0 parts of CMN and 135.3 parts of 50MB-26 were added to the polymer solution obtained above, and the reaction was carried out at 90°C for 5 hours. The amine value was measured by sampling and found to be 0.6 mg KOH / g (value as polymer solution), confirming that the quaternary ammonium salt conversion proceeded almost exactly as expected. The polymer solution containing the obtained polymer dispersant is called HVG-1. The theoretical solid content of the polymer dispersant calculated from the blending ratio in this polymer is 40.0%.

[0066] (Comparative Synthesis Example 2) · Polymer dispersant that does not contain quaternary ammonium salts In a reaction apparatus similar to that of Synthesis Example 1 equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, 71.0 parts (0.0400 mol) of 50MB-26, 70 parts (0.0342 mol) of PP2000D, 1.2 parts of αMS, 9.4 parts of St, and 19.4 parts of 4VP were placed in the reaction apparatus, and heated to 75°C while bubbling nitrogen gas. When the temperature reached 70°C, 4.5 parts of V601 were added as a polymerization initiator, and polymerization was carried out at 75°C for 4 hours. Furthermore, 2.0 parts of V601 were added, and polymerization was carried out at 75°C for 4 hours to obtain a polymer solution. The polymer was sampled and the molecular weight of the obtained polymer was measured, and the number average molecular weight (hereinafter abbreviated as Mn) was 23,400, the PDI was 1.92, and the PT was 36,800, and almost no peaks derived from the PP2000D used as the raw material were observed.

[0067] b) Introduction of unsaturated groups Next, 11.5 parts of MOI (0.0742 mol, the total number of moles of 50MB-26 and PP2000D) and 0.3 parts of DOS as a catalyst were added to the polymer solution obtained above, and reacted at 80 ° C. for 5 hours. When the solution was sampled and measured with an infrared spectrophotometer, it was confirmed that the peak derived from the isocyanate group had disappeared. Therefore, a polymer solution in which unsaturated groups were introduced into the polymer terminal and the terminal of 50MB-26 was obtained. The obtained polymer solution containing the polymer dispersant is called HVG-2. The theoretical solid content of the polymer dispersant calculated from the compounding ratio in this polymer is 62.5%.

[0068] (Comparative Synthesis Example 3) A polymer dispersant having a content of the general formula (1) of less than 45 parts and a content of a quaternary ammonium salt of more than 45 parts. In a reaction apparatus similar to that of Synthesis Example 1 equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, 71.0 parts (0.0400 mol) of 50MB-26, 50 parts (0.0472 mol) of AP1000D, 1.2 parts of αMS, 15.9 parts of St, and 32.9 parts of 4VP were placed in the reaction apparatus, and heated to 75°C while bubbling nitrogen gas. When the temperature reached 70°C, 4.5 parts of V601 were added as a polymerization initiator, and polymerization was carried out at 75°C for 4 hours. Furthermore, 2.0 parts of V601 were added, and polymerization was carried out at 75°C for 4 hours to obtain a polymer solution. The polymer was sampled and the molecular weight of the obtained polymer was measured, and the number average molecular weight (hereinafter abbreviated as Mn) was 12,600, the PDI was 1.83, and the PT was 25,100, and almost no peaks derived from AP1000D used as a raw material were observed. The molecular weights were measured in the same manner as above.

[0069] b) Introduction of unsaturated groups Next, 16.5 parts of MOI (0.1063 mol, the total number of moles of 50MB-26 and PP2000D) and 0.3 parts of DOS as a catalyst were added to the polymer solution obtained above, and the reaction was carried out at 80°C for 5 hours. When a sample was taken and measured with an infrared spectrophotometer, it was confirmed that the peak derived from the isocyanate group had disappeared. Therefore, a polymer solution in which unsaturated groups were introduced into the polymer terminals and the terminals of 50MB-26 was obtained.

[0070] c) Quaternary ammonium chloride Next, 31.0 parts of CMN and 150.4 parts of 50MB-26 were added to the polymer solution obtained above, and the reaction was carried out at 90°C for 5 hours. The amine value was measured by sampling and found to be 0.5 mg KOH / g (value as polymer solution), confirming that the quaternary salt conversion had progressed almost exactly as expected. The polymer solution containing the obtained polymer dispersant is called HVG-3. The theoretical solid content of the polymer dispersant calculated from the blending ratio in this polymer is 40.0%.

[0071] Table 2 shows the compositions and physical properties of the polymer solutions HVG-1 to HVG-3 containing the polymer dispersants obtained in Comparative Synthesis Examples 1 to 3.

[0072] [Table 2]

[0073] <Preparation of Carbon Nanotube (CNT) Dispersion> Example 1 0.2 parts of single-walled carbon nanotubes Tuball (manufactured by OCSiAl, average diameter: 1.2-2.0 nm, average length: 2-20 μm), 99.3 parts of methyl ethyl ketone (hereinafter abbreviated as MEK), 0.50 parts of polymer solution VG-1 (theoretical solid content 40.0%) containing a polymer dispersant, and 180 parts of zirconia beads (diameter 0.8 mmφ) were placed in a resin container. The CNTs were wetted but sunk to the bottom of the container, and there was a transparent layer on the top. When the dispersion treatment was performed for 60 minutes using Scandex, the liquid turned uniformly black, and the aggregated state of the CNTs was broken down. Next, the CNTs that were not sufficiently dispersed were precipitated and separated by centrifugation, and the supernatant was taken out as CNT dispersion liquid-1.

[0074] (Examples 2 to 12 and Comparative Examples 1 to 6) CNT dispersions-2 to-22 were prepared in the same manner as in Example 1 above, except that the compositions were as shown in Table 3. The meanings of the abbreviations in Table 3 are as follows. MWCNT: (Hamamatsu Carbonix, multi-walled carbon nanotubes, average diameter: 10-40 nm, average length: 500 μm-1,500 μm) SG101: (Product name "SG-101", Zeon Corporation, single-walled carbon nanotube, average diameter: 3-5 nm, average length: 100-600 μm) 100T: (Product name "K-nanos100T", manufactured by KUMHO, average diameter: 11-13 nm, average length: 40-50 μm)

[0075] [Table 3]

[0076] <Calculation of CNT Average Diameter and Average Length> The powder of CNTs was observed with an electron microscope, and the average diameter and average length were calculated for 10 randomly selected ones. This operation was carried out in 5 batches, and the numerical ranges for the average diameter and average length were determined.

[0077] <Evaluation of CNT Dispersion Liquid> Using an E-type viscometer (measurement conditions: 25°C, rotor rotation speed 100 rpm), the viscosities of the CNT dispersion liquid at 25°C immediately after dispersion (initial) and after standing for 10 days were measured. Then, based on the initial viscosity, the change rate of the viscosity after standing for 10 days (viscosity change rate (%)) was calculated, and the viscosity stability of the CNT dispersion liquid was evaluated according to the following evaluation criteria. Furthermore, the state of the CNT dispersion liquid after standing for 10 days was observed by optical microscope observation (200 times), and the presence or absence of aggregates was confirmed. ◎: The viscosity change rate was less than 5%. 〇: The viscosity change rate was 5% or more and less than 10%. ×: The viscosity change rate was 10% or more.

[0078] Also, the CNT concentration of the CNT dispersion liquid after centrifugation was measured. A spectrophotometer was used for the measurement of the CNT concentration. Specifically, the absorbance of a sample with a known CNT concentration was measured to create a calibration curve. Then, the absorbance of the sample diluted to a measurable concentration was measured, and the CNT concentration of the sample was calculated from the calibration curve. The ratio (%) of the CNT concentration after centrifugation to the designed CNT concentration was calculated as "dispersion stability (%)". The closer the dispersion stability is to 100%, the better the dispersibility of CNTs. The evaluation results of the CNT dispersion liquid are shown in Table 4.

[0079]

Table 4

[0080] The CNT dispersions dispersed using the polymer solution containing the polymer dispersant of the present invention all had excellent viscosity stability and dispersion stability, and no aggregates were observed after standing for 10 days. On the other hand, the CNT dispersions of Comparative Examples 2, 3, 5, and 6 used a polymer dispersant that does not contain a quaternary ammonium salt, or the ratio of the macromonomer deviated from that of the present invention, so the viscosity stability and dispersion stability were poor, and aggregates were also confirmed. However, in Comparative Examples 1 and 4, a polymer dispersant having no unsaturated group was used in the polymer. Perhaps because the presence or absence of the unsaturated group did not adversely affect the dispersibility, both had good viscosity stability and dispersion stability, and no aggregates were confirmed.

[0081] <Preparation of Carbon Black (CB) Dispersion> (Example 13) 3.0 parts of carbon black (trade name "Li-435", manufactured by Denka Co., Ltd., acetylene black) (CB), 89.5 parts of MEK, 7.50 parts of VG-1 (theoretical solid content 40.0%), and 180 parts of zirconia beads (diameter 0.8 mmφ) were placed in a resin container. The CB was wet but sank to the bottom of the container, and there was a transparent layer on the top. When dispersion treatment was carried out for 60 minutes using a Scandex, the liquid became uniformly black, and the aggregated state of the CB was resolved. Then, centrifugation was performed to sediment and separate the CB that was not sufficiently dispersed, and the supernatant was taken out as CB dispersion - 1.

[0082] (Examples 14 to 17, and Comparative Examples 7 and 8) CB dispersions - 2 to CB dispersions - 7 were prepared in the same manner as in Example 13 described above, except that the formulations shown in Table 5 were used.

[0083]

Table 5

[0084] <Evaluation of CB Dispersion> Using an E-type viscometer (measurement conditions: 25°C, rotor rotation speed 100 rpm), the viscosity of the CB dispersion immediately after dispersion (initial state) and after standing still for 10 days was measured at 25°C. The rate of change in viscosity after standing still for 10 days (viscosity change rate (%)) based on the initial viscosity was then calculated, and the viscosity stability of the CB dispersion was evaluated according to the following evaluation criteria. ⊚: Viscosity change rate was less than 5%. ◯: The viscosity change rate was 5% or more and less than 10%. ×: The viscosity change rate was 10% or more.

[0085] Furthermore, the state of the CB dispersion after standing for 10 days was observed under an optical microscope (200x) to confirm the presence or absence of aggregates. The evaluation results of the CB dispersion are shown in Table 6.

[0086] [Table 6]

[0087] All of the CB dispersions dispersed using the polymer solution containing the polymer dispersant of the present invention had excellent viscosity stability, and no aggregates were observed after being left to stand for 10 days. On the other hand, the CB dispersion of Comparative Example 8 had poor viscosity stability because the macromonomer ratio was outside the scope of the present invention, and aggregates were also observed. However, in Comparative Example 7, a polymer dispersant that does not have an unsaturated group in the polymer was used. In this case, the viscosity stability was good and no agglomerates were observed, probably because the presence or absence of an unsaturated group does not adversely affect the dispersibility.

[0088] <Production of Coating Composition> (Production Example 1) 50 parts of the CNT dispersion liquid-1 obtained in Example 1 was diluted with 100 parts of tripropylene glycol diacrylate (hereinafter, abbreviated as TPGDA), and 4 parts of a photopolymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad 184", manufactured by IGM Resins) was added and mixed until uniform, to obtain coating composition-1.

[0089] (Production Examples 2 to 17, and Comparative Production Examples 1 to 3) Coating composition-2 to coating composition-20 were obtained in the same manner as in Production Example 1 above, except that the compositions shown in Table 7 were used.

[0090] [Table 7]

[0091] <Production of cured film> (Application example 1) Coating composition-1 was applied to the treated surface of an easily adhesive PET film (Toyobo: A4160) to a dry film thickness of 14 g / m 2 The coating was applied with a D bar #14 so that the coating became evenly distributed, and then dried for 40 seconds using a dryer at 100°C. Next, a cured film was obtained by irradiating UV light using an 80W / cm high-pressure mercury lamp at 5m / min and one pass.

[0092] (Application Examples 2 to 17, and Comparative Application Examples 1 to 3) Coating composition-2 to coating composition-20 were used instead of coating composition-1 in Application Example 1, and cured films were obtained in the same manner as in Application Example 1.

[0093] <Evaluation> (Sliding property test) Using a Gakushin fastness tester (manufactured by Yasuda Seiki Co., Ltd.), a 1cm x 1cm flat friction plate with a gold width of No. 3 was attached and a sliding test was carried out under the conditions of a load of 500g and 60 reciprocations per minute. After rubbing, the film surface was visually observed and rated on a 5-point scale (1 poor to 5 excellent).

[0094] (Anti-blocking property test) The obtained cured film was cut into a size of 4 cm x 4 cm, and placed on the untreated surface of a PET film cut to the same size, and then subjected to a blocking test with a pressure of 4 kg / cm 2 The test was carried out for 24 hours in an atmosphere of 40° C. under a load of 1000 g / m. After the test, the performance was evaluated according to the following evaluation criteria. The results of the sliding property test and the anti-blocking property test are shown in Table 8. ◯: The cured film was easily peeled off without applying force. Δ: There was a slight delay before the cured film peeled off, but the interface was not wetted. ×: The cured film did not peel off, and the interface was wet.

[0095] [Table 8]

[0096] It was found that Application Examples 1 to 17, which were prepared using a polymer solution containing the pigment dispersant of the present invention, were excellent in curability, had a sliding property test score of 4 or more, and also performed well in the anti-blocking property test. On the other hand, in Comparative Application Examples 1 to 3, since the pigment dispersant does not contain an unsaturated group, the curability is poor, the sliding property test score is 2 or less, and the antiblocking property test score is also poor. [Industrial Applicability]

[0097] The carbon material dispersion of the present invention exhibits high dispersibility with high stability, and water-based paints, inks, plastic moldings, and the like obtained from the carbon dispersion can fully exhibit the properties of the carbon material, such as high electrical conductivity or high heat conductivity, and are suitable for various applications of the carbon material, such as battery materials, electronic component trays, IC chip covers, electromagnetic wave shields, automotive parts, and robot parts.

Claims

1. A polymer dispersant for dispersing at least one carbon material selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite, and graphene in a liquid medium, comprising: The polymer dispersant contains 45% by mass or more and 95% by mass or less of a structural unit (i) having a (meth)acryloyloxy group bonded to an end thereof, which is represented by the following general formula (1): 【Chemistry 1】 (In the general formula (1), R 1 and R 3 represents a hydrogen atom or a methyl group, R 2 Ha-CH 2 CH 2 -or-CH 2 CH 2 OCH 2 CH 2 -, m represents an arbitrary number of repetitions, and n represents 10 to 100. A polymer dispersing agent having ultraviolet curing properties, the polymer comprising: 3% by mass or more and 45% by mass or less of structural units (ii) derived from a monomer that is a quaternary ammonium salt of at least one basic monomer selected from the group consisting of 2-vinylpyridine, 4-vinylpyridine, 1-vinylimidazole, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate; and 2% by mass or more and 10% by mass or less of structural units (iii) derived from a vinyl-based monomer copolymerizable with the structural units (i) and the structural units (ii). The polymer dispersing agent has a number average molecular weight of 10,000 or more and 30,000 or less.

2. 2. The polymeric dispersant according to claim 1, wherein the quaternary ammonium salt of the basic monomer is a benzyl chloride salt, a naphthyl methyl chloride salt, or an anthracenyl methyl chloride salt of the basic monomer.

3. The polymer dispersant according to claim 1, wherein the vinyl monomer that constitutes the structural unit (iii) contains α-methylstyrene, and the content of the structural unit derived from α-methylstyrene in the polymer is 0.5% by mass or more and 5% by mass or less.

4. A polymer dispersant composition comprising the polymer dispersant according to any one of claims 1 to 3 and a monomer represented by the following general formula (2): 【Chemistry 2】 (In the above general formula (2), R 4 represents an alkyl group having 1 to 18 carbon atoms; R 5 represents an alkylene group or a branched alkylene group having 2 to 4 carbon atoms; R 6 Ha-CH 2 CH 2 -or-CH 2 CH 2 OCH 2 CH 2 - indicates R 7 represents hydrogen or a methyl group, and p represents 10 to 100.

5. A carbon material dispersion comprising the polymer dispersant according to any one of claims 1 to 3, the carbon material, and the liquid medium.

6. The carbon material dispersion liquid according to claim 5 , wherein the liquid medium contains at least one of an ultraviolet-curable monomer and an oligomer having one or more (meth)acryloyloxy groups.

7. 6. The carbon material dispersion according to claim 5, wherein a content of the polymer dispersant relative to 100 parts by mass of the carbon material is 10 parts by mass or more and 200 parts by mass or less, and a content of the carbon material relative to 100 mass% of the carbon material dispersion is 15 mass% or less.

Citation Information

Patent Citations

  • Nanocarbon dispersion

    JP2019019155A

  • Pigment dispersion

    JP2021075660A

  • Carbon material dispersion

    JP2022160216A

  • Coloring material dispersed liquid and photosensitive coloring resin composition

    WO2013175978A1

  • Ink containing carbon nanotube

    JP2010174084A